PENINGKATAN KOMPETENSI GURU SD DALAM MEMFASILITASI BELAJAR MENDALAM MELALUI BELAJAR KONTEKSTUAL DI KOTA BEKASI - Virzha Aulianna Dhaksietsatsura; Kunto Imbar Nursetyo; RA. Murti Kusuma Wirasti; Raden Roro Qisthi Aliika Larasati; Wafa Fatma (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to improve the competence of elementary school teachers in Bekasi City in facilitating deep learning through a contextual learning approach. The main problems addressed include the low results of the Teacher Competency Test (UKG), limited understanding of the deep learning concept among teachers, and the minimal implementation of contextual learning strategies in the classroom. To respond to these issues, the program was carried out through a series of activities such as awareness sessions, training, mentoring, and evaluation, all conducted in a participatory manner with the involvement of partner teachers. The evaluation was conducted through assignment-based assessments, where teachers developed contextual lesson modules, and through reaction-based participant feedback. The results showed an increase in teachers' ability to design relevant and contextual teaching strategies. In addition, participants showed strong enthusiasm for the materials, methods, and facilitators involved. This program is expected to contribute significantly to improving the quality of basic education in Bekasi City and serve as a model for teacher competence development through best practices.